2021
DOI: 10.1007/s00345-021-03753-y
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter external validation of the radical cystectomy pentafecta in a European cohort of patients undergoing robot-assisted radical cystectomy with intracorporeal urinary diversion for bladder cancer

Abstract: Objective To perform an external validation of this RC-pentafecta. Method Between January 2014 and December 2019, 104 consecutive patients who underwent RARC with ICUD within 6 urological centers were analyzed retrospectively. Patients who simultaneously demonstrated negative soft tissue surgical margins (STSMs), a lymph node (LN) yield ≥ 16, absence of major (Clavien–Dindo grade III–V) 90-day postoperative complications, absence of UD-related long-term se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 28 publications
(30 reference statements)
0
15
0
Order By: Relevance
“…Similar findings were reported by Laymon et al: only 33.6% of individuals who underwent open RC attained pentafecta, while the main reason for not achieving pentafecta was a low number of resected LNs (i.e., <16) (34). Another corresponding paper with our study by Baron et al revealed that pentafecta protocol in the cohort of patients undergoing robotassisted RC with intracorporeal UD was highly influenced by the number of resected LNs (56% of pentafecta attainment) leading to an overall pentafecta rate as of 39% (22).…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…Similar findings were reported by Laymon et al: only 33.6% of individuals who underwent open RC attained pentafecta, while the main reason for not achieving pentafecta was a low number of resected LNs (i.e., <16) (34). Another corresponding paper with our study by Baron et al revealed that pentafecta protocol in the cohort of patients undergoing robotassisted RC with intracorporeal UD was highly influenced by the number of resected LNs (56% of pentafecta attainment) leading to an overall pentafecta rate as of 39% (22).…”
Section: Discussionmentioning
confidence: 54%
“…This might reflect the fact that other factors were of more pronounced prognostic value (e.g., surgery modality, pT category, and UD type). Interestingly, other papers also did not directly show the independent prognostic significance of LN staging on trifecta (15) or pentafecta (22). In the recent paper by Oh et al, pentafecta failers were the predominant group, reaching over 71% (23).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations